Development of Climate Change Education Curriculum to Promote Climate Literacy of Lower Secondary School Students - Kongsing, Teejutha; Kaewdee, Sakolrat (An Online Journal of Education, 2023)
The purpose of this research was to develop a climate change education curriculum for lower secondary school students. The participants in this research were: 1) six interviewees from the field of climate change or environmental education, and 2) three curriculum and course document evaluators. The research used a descriptive research methodology. The tools used for the research consisted of 1) an opinion interview form about the climate change education curriculum and 2) an assessment form on the suitability and consistency of the curriculum and course documents. The results showed: 1. A climate change education curriculum should: 1) focus on the dimensions of economy and social and global citizenship, including topics regarding adaptation, mitigation, and climate resilience, 2) utilize a teaching approach that incorporates a situation- and problem-based learning model, and 3) adapt to the context of students in each area to manage learning. 2. The curriculum developed by the researcher consisted of 4 learning units. The assessment of the curriculum showed mean scores at a strongly agreed level (M=2.7, SD=0.29); assessment scores of the course documents from Unit 1 showed mean scores at a moderately agreed level (M=2.47, SD=0.29), while those from Unit 2 showed mean scores at a moderately agreed level (M=2.37, SD=0.22), those from Unit 3 showed mean scores at a strongly agreed level (M=2.67, SD=0.21), and those from Unit 4 showed mean scores at a strongly agreed level (M=2.62, SD=0.34).